2015
DOI: 10.2134/jeq2015.01.0043
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Color-based Tracers and Classifying Sediment Sources in the Assessment of Sediment Dynamics Using Sediment Source Fingerprinting

Abstract: The use of sediment color as a fingerprint property to determine sediment sources is an emerging technique that can provide a rapid and inexpensive means of investigating sediment sources. The present study aims to test the feasibility of color fingerprint properties to apportion sediment sources within the South Tobacco Creek Watershed (74 km 2 ) in Manitoba, Canada. Suspended sediment from 2009 to 2011 at six monitoring stations and potential source samples along the main stem of the creek were collected. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 48 publications
0
32
2
Order By: Relevance
“…Furthermore, within a watershed, Carter et al (2003) reported a spatial difference in primary sediment sources between the upper and lower reaches due to land use difference, for the River Aire watershed, UK. Similarly, Koiter et al (2013a) and Barthod et al (2015) reported a shift of the dominant sediment source along the stream within the South Tobacco Creek watershed, MB, Canada, as a result of a dramatic change in the topography and due to variations in the connectivity between hillslopes and the stream channel. Thus, there is considerable variation in the dominant sediment sources both within and between watersheds, which means that site-specific assessment is often required to underpin meaningful management advice.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Furthermore, within a watershed, Carter et al (2003) reported a spatial difference in primary sediment sources between the upper and lower reaches due to land use difference, for the River Aire watershed, UK. Similarly, Koiter et al (2013a) and Barthod et al (2015) reported a shift of the dominant sediment source along the stream within the South Tobacco Creek watershed, MB, Canada, as a result of a dramatic change in the topography and due to variations in the connectivity between hillslopes and the stream channel. Thus, there is considerable variation in the dominant sediment sources both within and between watersheds, which means that site-specific assessment is often required to underpin meaningful management advice.…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies (Koiter et al 2013a;Barthod et al 2015) at the South Tobacco Creek watershed, MB, Canada, demonstrated that soil colour-based fingerprints predicted similar source apportionment as fallout radionuclides (i.e., 137 Cs) and geochemical properties. Recently, the fingerprinting technique using colour-based tracers has proved to be a cost-effective alternative in estimating source contributions to suspended sediments in a range of environments (Martinez-Carreras et al 2010;Brosinsky et al 2014;Barthod et al 2015).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations